PENGARUH PRODUK DOMESTIK REGIONAL BRUTO (PDRB) DAN TINGKAT PENGANGGURAN TERBUKA (TPT) TERHADAP INDEKS PEMBANGUNAN MANUSIA (IPM) DI KABUPATEN BERAU - Rustam (Prodi Ekonomi Pembangunan, Universitas Muhammadiyah Berau, 2025)
The purpose of this study was to determine the effect of Gross Regional Domestic Product (GRDP) and Open Unemployment Rate (TPT) partially and simultaneously on the Human Development Index (HDI) in Berau Regency. Secondary data used in the form of time series data in 2017-2022, in the form of Human Development Index (HDI) data, Gross Regional Domestic Product (GRDP) data, and Open Unemployment Rate (TPT) data in Berau Regency. The analysis tools used are: classical assumption test (normality test, autocorrelation test, multicollinearity test, heteroscedasticity test), multiple linear regression analysis, correlation coefficient, determination coefficient, t-test, and F-test. The conclusion of the results of this study are: 1) Gross Regional Domestic Product (GRDP) has a significant partial influence on the Human Development Index (HDI) in Berau Regency. This is evidenced by the t-count value which is greater than the t-table value (3.939> 3.183) with a significance value less than the probability value (0.029 < 0.05); 2) The Open Unemployment Rate (TPT) does not have a significant partial influence on the Human Development Index (HDI) in Berau Regency. This is based on the t-count value which is smaller than the t-table value (-2.635 < 3.183) with a significance value greater than the probability value (0.078 > 0.05); 3) Gross Regional Domestic Product (GRDP) and the Open Unemployment Rate (TPT) have a significant simultaneous influence on the Human Development Index (HDI) in Berau Regency. Proven based on the F test where the F- calculated value is greater than the F-table (15.095 > 9.55) with a significance value smaller than the probability value (0.027 < 0.05).